Konstruksi Perjanjian Finansial Teknologi Pembiayaan Multiguna Shopee Pay Later Pada E-Commerce Shopee Indonesia - Qomariyah, Lailatul; Fitriyah, Mas Anienda Tien (Legal Spirit, 2023)
The convenience provided by online loans has a risk if the debtor fails to pay, especially since there is no guarantee in this online loan system. This, of course, will be disastrous for creditors. Shopee Pay Later, one of the marketplace-based online loan providers from the Shopee application, provides loans for users through the distribution of multipurpose financing online without collateral. This research uses a normative-juridical method. The SPayLater multipurpose financing agreement, literature studies, and laws and regulations are the data sources. Conceptual and statutory approaches become the basis for further qualitative analysis, which is explained descriptively and analytically so as to obtain systematic results and conclusions related to the problems studied. Based on the findings of this research, the P2PL fintech financing agreement has been legally regulated in Financial Services Authority Regulation No. 10/POJK. 05/2022 concerning information technology-based money lending and borrowing services (LPBBTI). The SPayLater multipurpose financing agreement has been made in accordance with applicable legal provisions and fulfils the legal requirements of the agreement. This financing agreement forms a legal relationship between the creditor and the debtor. The service provider only acts as an intermediary for the creditor in selecting prospective debtors and resolving disputes internally so that the parties can immediately fulfil their respective obligations.